Pengaruh Customer Experience terhadap Loyalitas Pelanggan Seblak Prasmanan Teh Windy di Karawang - Ifada, Aulia; Rizqiyanti, Davina Meita; Yusuf, Abdul (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research discusses whether customer experience influences customer loyalty at Seblak Teh Windy in Karawang. This research uses simple linear regression analysis and descriptive data in written and spoken words from the objects observed. The data collection technique in this research was a questionnaire; the population in this research was all people who had tried Seblak Windy Tea in Karawang, while the sample used in this research was 106 respondents. Variable X in this research is Customer Experience with Sense, feel, think, act, and related indicators. Meanwhile, Variable Y in this research is Customer Loyalty with Repeat purchase, retention, and referrals indicators. From the results of testing the feasibility of the model (F Test), the result is that the simple linear regression model cannot be used to predict Customer Loyalty, which is influenced by Customer Experience, as evidenced by the calculated F value being greater than the significant value, the simple linear regression model cannot be used to predict Customer Loyalty which is influenced by Customer Experience. Meanwhile, the correlation test (r) has a strong influence